CYLD expression in dendritic cells involved in the immunoregulation of pulmonary adenocarcinoma via NF-κB pathway. Issue 1 (1st January 2020) - Yu, Qinghua; Lei, Yujie; Huang, Yunchao; Zhang, Jiguang; Chen, Yangming; Chen, Kai; Lin, Jianbin; Sun, Shihui; Lin, Xing
Abstract: Our previous study found that IL33 repressed the growth of pulmonary adenocarcinoma (PA) via regulation of dendritic cells (DCs). However, the molecular mechanism of DCs in PA is still unclear. The present work showed that CYLD −/− mice have a shorter survival rate of PA, and knockout CYLD in DCs also repress the progression of PA in mice. Subsequently, we found that decreased expression and reduced the nuclear translocation of NF-κB signalling was observed in CYLD knockout DCs, and inhibiting NF-κB pathway repressed DCs-induced proliferation and function of CD4 + T cells. These results indicated that CYLD function as a tumour suppresser in PA via regulates the function of DCs through NF-κB signalling pathway. Our findings support that CYLD serves as a potential target for immunotherapy in PA.